Skin Microbiomes of California Terrestrial Salamanders Are Influenced by Habitat More Than Host Phylogeny - Bird, Alicia K.; Prado-Irwin, Sofia R.; Vredenburg, Vance T.; Zink, Andrew G. (Frontiers in Microbiology, 2018)
A multitude of microorganisms live on and within plant and animal hosts, yet the ecology and evolution of these microbial communities remains poorly understood in many taxa. This study examined the extent to which environmental factors and host taxonomic identity explain microbiome variation within two salamander genera, Ensatina and Batrachoseps, in the family Plethodontidae. In particular we assessed whether microbiome differentiation paralleled host genetic distance at three levels of taxonomy: genus and high and low clade levels within Ensatina eschscholtzii. We predicted that more genetically related host populations would have more similar microbiomes than more distantly related host populations. We found that salamander microbiomes possess bacterial species that are most likely acquired from their surrounding soil environment, but the relative representation of those bacterial species is significantly different on the skin of salamanders compared to soil. We found differences in skin microbiome alpha diversity among Ensatina higher and lower clade groups, as well as differences between Ensatina and Batrachoseps. We also found that relative microbiome composition (beta diversity) did vary between Ensatina lower clades, but differences were driven by only a few clades and not correlated to clade genetic distances. We conclude this difference was likely a result of Ensatina lower clades being associated with geographic location and habitat type, as salamander identity at higher taxonomic levels (genus and Ensatina higher clades) was a weak predictor of microbiome composition. These results lead us to conclude that environmental factors are likely playing a more significant role in salamander cutaneous microbiome assemblages than host-specific traits.